2017
DOI: 10.1007/s11367-017-1384-x
|View full text |Cite|
|
Sign up to set email alerts
|

New and updated life cycle inventories for surfactants used in European detergents: summary of the ERASM surfactant life cycle and ecofootprinting project

Abstract: Purpose Cradle-to-gate life cycle inventories (LCIs) for the production of a series of common surfactants used in European detergents and personal care products have been voluntarily compiled by 14 major companies collaborating within ERASM (www.erasm.org). The study builds on a similar project executed by CEFIC-Franklin (1994) and summarised by Stalmans et al. (Tenside Surf Det 32:84-109, 1995). The data are targeted as an industry-agreed and representative market average for surfactants in Europe for the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 12 publications
(5 reference statements)
0
21
0
Order By: Relevance
“…Numerous studies from various laboratories in the past 40 years [78,103,175,178,200,201] indicated that this linear relationship in equations (13)(14) is essentially valid but with very different KA values in the original (1-2) equations. Other researchers adjusted their equations for an essentially constant value of KA for all surfactants, which is not true due to the large number of new surfactant molecules designed for different applications in recent years.…”
Section: The Normalized Hydrophilic-lipophilic Deviation (Hldn) As a ...mentioning
confidence: 99%
“…Numerous studies from various laboratories in the past 40 years [78,103,175,178,200,201] indicated that this linear relationship in equations (13)(14) is essentially valid but with very different KA values in the original (1-2) equations. Other researchers adjusted their equations for an essentially constant value of KA for all surfactants, which is not true due to the large number of new surfactant molecules designed for different applications in recent years.…”
Section: The Normalized Hydrophilic-lipophilic Deviation (Hldn) As a ...mentioning
confidence: 99%
“…Numerous studies from various laboratories in the past 40 years [78,103,176,179,200,201] indicated that this linear relationship in equations (13)(14) is essentially valid but with very different KA values in the original (1-2) equations. Other researchers adjusted their equations for an essentially constant value of KA for all surfactants, which is not true due to the large number of new surfactant molecules designed for different applications in recent years.…”
Section: The Normalized Hydrophilic-lipophilic Deviation (Hldn) As a ...mentioning
confidence: 99%
“…The linear alkylbenzene sulphonic acid is considered as the proxy for the EOR surfactants. The total energy consumption for these surfactants is 62 MJ/kg-surfactant, and their manufacturing results in a total CO 2 emission of 1.75 kg CO 2 per kg surfactant 23 . In the manufacturing of these surfactants, different sources of primary energy from renewable and fossil fuels are used (although the Exergy recovery factor.…”
Section: Work Streamsmentioning
confidence: 99%